Aqueous-solution-processable metal oxides for high-performance organic and perovskite solar cells. Issue 36 (4th September 2017) - Lou, Yan-Hui; Wang, Zhao-Kui
Abstract : Poly(3, 4-ethylene dioxythiophene):poly(4-styrenesulfonate) (PEDOT:PSS) is a widely utilized hole-transporting material (HTM) in planar photovoltaic devices, such as organic solar cells (OSCs) and perovskite solar cells (PSCs). Abstract : Poly(3, 4-ethylene dioxythiophene):poly(4-styrenesulfonate) (PEDOT:PSS) is a widely utilized hole-transporting material (HTM) in planar photovoltaic devices, such as organic solar cells (OSCs) and perovskite solar cells (PSCs). However, the hygroscopic nature of PEDOT:PSS aqueous dispersions may restrict their future application. Therefore, it is necessary to develop other effective and stable HTMs to achieve high-performance photovoltaic devices. Herein, we demonstrate a facile route to deposit solution-processed MoO3, GeO2, V2 O5 and CrO3 thin films as hole-transporting layers by directly dissolving their commercial powders in deionized water. Among these, the solution-processed V2 O5 ( s V2 O5 ) film exhibited the highest work function of 5.2 eV, and the best hydrophobicity, with a contact angle of 77.2°. The s V2 O5 -based OSCs and PSCs presented power conversion efficiencies (PCEs) of 8.36% and 14.13%, respectively. Notably, the PEDOT:PSS V2 O5 composite HTM based device obtained a maximum PCE of 18.03% with a V oc exceeding 1.0 V. These aqueous-solution-processed HTMs have potential applications in green and low-cost photovoltaic devices by virtue of their simple and ecofriendly preparations.